2019
DOI: 10.1002/phar.2295
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin Thromboprophylaxis Dosing and Anti–Factor Xa Levels in Low‐Weight Patients

Abstract: Introduction Enoxaparin is a widely used anticoagulant to prevent venous thromboembolism (VTE). A fixed dose is recommended for VTE prophylaxis. However, fixed prophylactic doses of enoxaparin in low‐weight patients may be close to the weight‐based dosing recommended for VTE treatment. Objective To evaluate peak anti–factor Xa (aFXa) levels in low‐weight patients receiving enoxaparin for VTE prophylaxis. Methods Retrospective cohort of adult patients weighing < 55 kg who were hospitalized at Loma Linda Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…This difference could be explained by the variability of enoxaparin doses used in the retrospective study, with majority of patients received 30 mg once daily. 19 The median dose of enoxaparin administered in the retrospective study (0.6 mg per kg) was similar to that in our study (0.66 mg per kg). Both median doses are lower than that used by Rojas et al who prospectively administered 40 mg enoxaparin to 56 patients weighing < 55 kg, for a calculated median dose of 0.8 mg per kg.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This difference could be explained by the variability of enoxaparin doses used in the retrospective study, with majority of patients received 30 mg once daily. 19 The median dose of enoxaparin administered in the retrospective study (0.6 mg per kg) was similar to that in our study (0.66 mg per kg). Both median doses are lower than that used by Rojas et al who prospectively administered 40 mg enoxaparin to 56 patients weighing < 55 kg, for a calculated median dose of 0.8 mg per kg.…”
Section: Discussionsupporting
confidence: 85%
“…Of note, the definition of low bodyweight was inconsistent among studies assessing enoxaparin prophylaxis, with <55 kg set as a cutoff weight in some studies, irrespective of patient sex. 19,20 A prospective study found a significant increase in bleeding risk among patients receiving enoxaparin for VTE treatment and weighing <55 kg. 27 However, that study assessed a therapeutic dose of enoxaparin (1 mg per kg every 12 hours) for the treatment of an established VTE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that standard dosing of prophylactic enoxaparin may represent an over dosage of enoxaparin in low weight patients as current evidence based on anti-factor-Xa data shows that reduced dosing may better achieve target levels of anticoagulation. 8 Of the 171 patients enrolled in our study, a greater percentage of patients were receiving standard dosing of enoxaparin VTE prophylaxis. This potentially could have led to an underpowered reduced dosing group.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis was supported by prior literature proposing that over-anticoagulation may occur with standard prophylactic LMWH dosing in low body weight patients based on anti-factor Xa level monitoring and that bleeding risk may also increase with advanced age and reduced body weight. 16,17…”
Section: Methodsmentioning
confidence: 99%